xy+53-x=21x-y(7+x)

Simple and best practice solution for xy+53-x=21x-y(7+x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for xy+53-x=21x-y(7+x) equation:


Simplifying
xy + 53 + -1x = 21x + -1y(7 + x)

Reorder the terms:
53 + -1x + xy = 21x + -1y(7 + x)
53 + -1x + xy = 21x + (7 * -1y + x * -1y)

Reorder the terms:
53 + -1x + xy = 21x + (-1xy + -7y)
53 + -1x + xy = 21x + (-1xy + -7y)

Solving
53 + -1x + xy = 21x + -1xy + -7y

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-21x' to each side of the equation.
53 + -1x + -21x + xy = 21x + -1xy + -21x + -7y

Combine like terms: -1x + -21x = -22x
53 + -22x + xy = 21x + -1xy + -21x + -7y

Reorder the terms:
53 + -22x + xy = 21x + -21x + -1xy + -7y

Combine like terms: 21x + -21x = 0
53 + -22x + xy = 0 + -1xy + -7y
53 + -22x + xy = -1xy + -7y

Add 'xy' to each side of the equation.
53 + -22x + xy + xy = -1xy + xy + -7y

Combine like terms: xy + xy = 2xy
53 + -22x + 2xy = -1xy + xy + -7y

Combine like terms: -1xy + xy = 0
53 + -22x + 2xy = 0 + -7y
53 + -22x + 2xy = -7y

Add '-53' to each side of the equation.
53 + -22x + -53 + 2xy = -53 + -7y

Reorder the terms:
53 + -53 + -22x + 2xy = -53 + -7y

Combine like terms: 53 + -53 = 0
0 + -22x + 2xy = -53 + -7y
-22x + 2xy = -53 + -7y

Reorder the terms:
53 + -22x + 2xy + 7y = -53 + -7y + 53 + 7y

Reorder the terms:
53 + -22x + 2xy + 7y = -53 + 53 + -7y + 7y

Combine like terms: -53 + 53 = 0
53 + -22x + 2xy + 7y = 0 + -7y + 7y
53 + -22x + 2xy + 7y = -7y + 7y

Combine like terms: -7y + 7y = 0
53 + -22x + 2xy + 7y = 0

The solution to this equation could not be determined.

See similar equations:

| w=-1 | | 26=4x+2y | | 4(x-y)-2(y-x)+3x(y-2)= | | y=x^3-10x^2+12x+6 | | 725+10.25x+19.50x=2500 | | 9(x+4)=59 | | 3x-21=2x-5 | | 8+X=-19 | | 10.6t+0.08-4.5t=1.97+8.8t | | f(120)=480-4*120 | | -14h-3h+3=-16h+15 | | 4k^2-2(-k+12)=86 | | 3.3(b-16)-4=5.9 | | 200-2x=50 | | 2(f-9)+8=14 | | 2(c+2.4)+7=15.6 | | 11x^2-208x-19=0 | | -12.3g-8.96=-16.46-12.9g | | 4k^2+2k+62=0 | | 6(y+1)2(3-y)=7y | | -4(k+18)+11=11 | | 0.1+(-0.1)=-0.2 | | 2s+4= | | 2x(2x+y-4)= | | x^2+x^2+16x+64=4x^2-16x+64 | | 2k^2-6k-5=0 | | 2(2x-3y+4)+2x(y-x)= | | (3xy^3-5xy+7y^2)=equation | | 6x^3-6x^2+15x=0 | | x=3*5-x | | -16t^2+96t+8=148 | | f(5)=3*5-6 |

Equations solver categories